Comparative analysis of 84 chloroplast genomes of Tylosema esculentum reveals two distinct cytotypes - Li, Jin; Cullis, Christopher (Frontiers in Plant Science, 2023)
Tylosema esculentum (marama bean) is an important orphan legume from southern Africa that has long been considered to have the potential to be domesticated as a crop. The chloroplast genomes of 84 marama samples collected from various geographical locations in Namibia and Pretoria were compared in this study. The cp genomes were analyzed for diversity, including SNPs, indels, structural alterations, and heteroplasmy. The marama cp genomes ranged in length from 161,537 bp to 161,580 bp and contained the same sets of genes, including 84 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The genes rpoC2 and rpoB, and the intergenic spacers trnT-trnL and ndhG-ndhI were found to be more diverse than other regions of the marama plastome. 15 haplotypes were found to be divided into two groups, differing at 122 loci and at a 230 bp inversion. One type appears to have greater variability within the major genome present, and variations amongst individuals with this type of chloroplast genome seems to be distributed within specific geographic regions but with very limited sampling for some regions. However, deep sequencing has identified that within most of the individuals, both types of chloroplast genomes are present, albeit one is generally at a very low frequency. The inheritance of this complex of chloroplast genomes appears to be fairly constant, providing a conundrum of how the two genomes co-exist and are propagated through generations. The possible consequences for adaptation to the harsh environment in which T. esculentum survives are considered. The results pave the way for marama variety identification, as well as for understanding the origin and evolution of the bean.